Master drummer : fundamental techniques - Walden, Ken ([EE.UU.] : A Secrets of the Pros, 2010)
El dvd es una entrevista con actuaciones musicales del baterista Dennis Chambers.
Dolby digital
Featuring Dennis Chambers accompanied by Benny Rietveld
Diálogo en inglés
Keywords: MUSICA; VIDEOGRABACIONES